Synthesis and Anthelmintic Activity of 3,6-Disubstituted-7H-s-triazolo(3,4-b) (1,3,4) thiadiazines - Nadkarni, Bharati A.; Kamat, Vijayalaxmi R.; Khadse, Barsu G. (Arzneimittelforschung, 2001)
A series of 3,6-disubstituted-7H-s-triazolo(3,4-b)(l,3,4)thiadiazines was synthesized by the condensation of the appropriate 3-substituted-4-amino-5-mercapto (1,2,4) triazoles with substituted phena-cyl bromides in alcoholic medium. These compounds have been studied for their in vivo anthelmintic activity in albino mice. A number of compounds showed promising activity when given by the oral route.
Keywords: Anthelmintics; Hymenolepis nana; Triazolo-thiadiazines, anthelmintic activity, mouse, synthesis